Lagu Salam Sahabat Anak Sebagai Inspirasi Penciptaan Karya Komposisi Tari - Daruni, Daruni (Institut Seni Indonesia Yogyakarta, 2022)
ABSTRACT. The series of beautiful, rhythmic and comical tones leave an impression of joy for the listeners. Once a musical work was auditive stimulated by Studio Omah Cangkem's entitled Salam Sahabat Anak, it prompted the birth of a dance work with the same title as the accompanying music. Following the title and the song's lyrics, the dance tells about the importance of making friends with children. The dance method of Jacqueline Smith was chosen to realize this dance design with the steps of dance design starting with listening and analyzing the structure of the song, which was identified as a varied composition of instrumental and vocals. The pattern of the musical framework and vocal variations became the basis for the selection of motifs and movement patterns and their variations. The concept of Creative Dance is also an option in this dance. The design aims to realize the Sahabat Anak dance, this pure dance type, to explore simple motion motifs according to the musical pattern. It is expected this simple dance can attract children's talents and encourage children to have a new perspective in which dancing is everyone's right; dancing is to set the heart; dance is for all; dance is an element of life; dancing makes life more beautiful, and dance makes life stronger to face various situations.ABSTRAK. Rangkaian nada indah, ritmik dan komikal meninggalkan kesan suka cita bagi pendengarnya. Dirangsang secara auditif dari karya musik Studio Omah Cangkem yang berjudul Salam Sahabat Anak, mendorong lahirnya karya tari yang diberi judul sama dengan musik pengiringanya. Sesuai dengan judul dan syair lagu yang terkandung di dalamnya maka tarian ini ini menceritakan tentang pentingnya bersahabat bagi anak-anak. Metode perancangan dimulai dengan mendengarkan, menganalisis struktur lagunya yang diidentifikasi sebagai sebuah komposisi bervariasi instrumental dan vokal. Pola kerangka musik dan variasi vocal menjadi landasan pemilihan motif dan pola gerak beserta variasinya serta konsep tari kreatif juga menjadi pilihan dalam perancangan karya ini. Perwujudan karya tari Sahabat Anak, bertipe tari murni dengan mengeksplor motif gerak sederhana sesuai pola musiknya. Harapan tarian sederhana ini dapat mengundang minat bakat anak dan mendorong anak memiliki citra baru bahwa menari itu hak siapa saja, menari itu menata hati, dance for all, dance as an element of life, menari itu membuat hidup lebih indah, membuat hidup lebih kuat menghadapi aneka situasi.